POLYSEMY IN CONTRACTS ESTABLISHING AN EMPLOYMENT RELATIONSHIP UNDER THE LAW OF ENGLAND AND WALES – A CASE STUDY - KIZIŃSKA, Anna (Comparative Legilinguistics, 2017)
In the first part of the article, by way of an introduction the unique features of the style of English legal language as well as the term polysemy from the cognitive linguistics point of view are presented. The second part demonstrates the analysis of the semantic frame of contracts establishing an employment relationship, its obligatory and optional sections (inter alia: termination of employment, probationary period and confidentiality). Next, the key polysemic words and expressions appearing in the contracts in question together with examples of their legal and colloquial meaning (to terminate, a termination, to second, a remedy, to settle, to govern etc.) are discussed. Subsequently, the paper concentrates on both polysemic words and expressions supporting key expressions as well as other polysemic expressions (amalgamation, a schedule, to incorporate) to present their meanings in various contexts. The research was carried out on ten model employment and internship contracts as well as secondment agreements under the law of England and Wales by virtue of which an employment relationship is formed.